Behavior of salivary testosterone and cortisol in men during an Ironman triathlon - Vaamonde, D.; García-Manso, J. M.; Algar-Santacruz, C.; Abbasi A, A.; Sarmiento, S.; Valverde-Esteve, T. (European Journal of Sport Science, 2022)
Endurance exercise induces notable acute hormonal responses on the gonadal and adrenal hormones. The purpose of this study was to assess the changes in salivary testosterone (Ts), salivary cortisol (Cs) and T/C ratio during long-distance triathlon. Ten well-trained male triathletes participated in the study and were assessed for hormonal changes at four time-points (pre-competition, post-swimming, post-cycling, and post-running phases). Ts decreased from pre-competition to post-swimming (from 93.37 pg/mL to 57.63 pg/mL; p < .01) and increased during two other parts of the competition to almost pre-competition values (cycling: 79.20 pg/mL, p = .02; running: 89,66 pg/mL, p = .04, respectively). Cs showed a similar behavior; decreasing in the post-swimming phase (1.74 pg/mL) and increasing in the other transitions (post-cycling: 7.30 pg/mL; post-running: 13.31 pg/mL), with significant differences between pre-competition and post- competition values (p = .01). Conversely, T/C increased significantly from pre-competition to post-swimming phase (p = .04) to later decrease until the end of the competition. Overall, T/C significantly decreased (p < .05). In conclusion, during an Ironman triathlon, hormone values fluctuate in response to the demands of the competition. Ts and Cs decrease after-swimming, increase after-cycling and reach the maximum values after-running. T/C reflects overall catabolic status.